Comparison of chemical profiles, antioxidation, inhibition of skin extracellular matrix degradation, and anti-tyrosinase activity between mycelium and fruiting body of Cordyceps militaris and Isaria tenuipes - Adchara Prommaban; Suwannee Sriyab; Pachabadee Marsup; Waranya Neimkhum; Jakkapan Sirithunyalug; Songyot Anuchapreeda; Chaiwat To-anun; Wantida Chaiyana (Taylor & Francis Group, 2022)
Context Cordyceps militaris and Isaria tenuipes (Cordycipitaceae) are high-value fungi that are used for health-promoting food supplements. Since laboratory cultivation has begun for these fungi, increased output has been achieved. Objective This study compared the chemical profiles, antioxidant, anti-tyrosinase, and skin extracellular matrix degradation inhibition between mycelium and fruiting body of C. militaris and I. tenuipes. Materials and methods The antioxidative potential of 10% v/v aqueous infused extract from each fungus was separately investigated using 2,2-azinobis(3-ethylbenzo-thiazoline-6-sulphonic acid) (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant ability, and ferric thiocyanate methods. The inhibition against MMP-1, elastase, and hyaluronidase were determined to reveal their anti-wrinkle potential. Anti-tyrosinase activities were determined. Results C. militaris and I. tenuipes extracts were found to contain a wide range of bioactive compounds, including phenolics, flavonoids, and adenosine. A correlation was discovered between the chemical compositions and their biological activities. The extract from I. tenuipes fruiting body (IF) was highlighted as an extraordinary elastase inhibitor (IC50 = 0.006 ± 0.004 mg/mL), hyaluronidase inhibitor (IC50: 30.3 ± 3.2 mg/mL), and antioxidant via radical scavenging (ABTS IC50: 0.22 ± 0.02 mg/mL; DPPH IC50: 0.05 ± 0.02 mg/mL), thereby reducing ability (EC1: 95.3 ± 4.8 mM FeSO4/g extract) and lipid peroxidation prevention (IC50: 0.40 ± 0.11 mg/mL). IF had a three-times higher EC1 value than ascorbic acid and significantly higher elastase inhibition than epigallocatechin gallate. Discussion and conclusions IF is proposed as a powerful natural extract with antioxidant and anti-wrinkle properties; therefore, it is suggested for further use in pharmaceutical, cosmeceutical, and nutraceutical industries.